Penerapan Multimedia Interaktif Google Sites pada Pembuatan Macam-Macam Pola Lengan untuk Meningkatkan Hasil Belajar Siswa Tata Busana SMKN 1 Bagor - Alvi Anggraini Harianto; Marniati Marniati; Imami Arum Tri Rahayu; Peppy Mayasari (Departement of Mathematics Education, 2024)
This research is classroom action research (PTK) which aims to describe the process of implementing interactive multimedia Google Sites, student responses, and student learning outcomes on material for making various sleeves patterns. This PTK was carried out at SMKN 1 Bagor for the 2023/2024 academic year. The research subjects were class X BB 2 students, totaling 36 students. The data collection method uses; observation, questionnaires, cognitive tests and psychomotor tests, with quantitative descriptive data analysis techniques. The research results prove that the application of interactive multimedia Google Sites in the very good category, student responses show that students strongly agree, and student learning outcomes in the material for making various sleeves patterns have increased. The findings of this research are that interactive multimedia Google Sites can improve the learning outcomes of class.